Girls and Boys: Economic Crisis, Fertility, and Birth Outcomes - Soohyung Lee; Chiara Orsini (Institute of Labor Economics (IZA), 2018)
We investigate the impact of an economic downturn on natality and birthweight for newborns when parents prefer sons. We examine South Korea, unexpectedly hit by the Asian financial crisis in 1997. For identification, we exploit regional and time variation in the crisis, focusing on women who were already pregnant when the downturn began. We find that the number of girls would have been 2 percent higher absent the crisis and that birth outcomes for girls were no better than those for boys, findings that differ from the Trivers-Willard Hypothesis. This relative disadvantage of girls is more severe among newborns who have at least two older siblings.
Keywords: H0; I1; J1; 330; fertility; birth outcomes; economic crisis; sex ratio; Trivers-Willard Hypothesis; scarring